The Validity of Research-Based Teaching Supplements to Improve Students' Scientific Literacy - Adystia, Yusdike; Lisdiana, Lisdiana; Yuniastuti, Ari (Journal of Innovative Science Education, 2023)
The development of teaching supplements based on research results regarding the dangers of vaping needs to be conducted considering that there is no integration regarding the dangers of vaping in biology subjects. Students need to improve information about the dangers of vaping through scientific literacy. The data collection techniques in this study consisted of a questionnaire. Through the data collection, the instruments needed in this study include validation sheets of material experts and media experts. The data were analyzed quantitatively to determine the category of validity and deepened by qualitative analysis. Based on the results of expert validation, research-based teaching supplements regarding the dangers of vaping were generally very valid with the average validation score of the two validators being 94.45%. The material contained in the teaching supplement was also adapted to current scientific developments related to the dangers of vaping by following scientific literacy indicators. The effectiveness of teaching supplements was determined based on the N-Gain value, the N-Gain value obtained was 0.76 which is in the High category